2014
DOI: 10.1186/2050-7771-2-13
|View full text |Cite
|
Sign up to set email alerts
|

Circumventing qPCR inhibition to amplify miRNAs in plasma

Abstract: BackgroundCirculating microRNAs (c-miRNAs) have be identified in saliva, urine and blood, which has led to increasing interest in their development as biomarkers for diverse diseases including cancers. One of the key advantages of c-miRNAs over other biomarkers is the ability to be amplified and quantified by quantitative PCR (qPCR). However, at phlebotomy when whole blood is dispensed into heparinized tubes, residual levels of the anti-coagulant lithium heparin may remain in the plasma and hence with RNA isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…RNA quality was assessed using threshold cycle (Ct) measurement of two endogenous miRNAs (miR-150 and miR-451) and a synthetic miRNA sequence, cel-miR-257, in randomly selected samples from each batch. Samples with Ct<35 for endogenous miRNAs and Ct<26.5 for cel-miR-257 were deemed of satisfactory quality, based on previous reports and guidelines 24–26 . All RNA samples were labeled using the same standardized protocols.…”
Section: Methodsmentioning
confidence: 99%
“…RNA quality was assessed using threshold cycle (Ct) measurement of two endogenous miRNAs (miR-150 and miR-451) and a synthetic miRNA sequence, cel-miR-257, in randomly selected samples from each batch. Samples with Ct<35 for endogenous miRNAs and Ct<26.5 for cel-miR-257 were deemed of satisfactory quality, based on previous reports and guidelines 24–26 . All RNA samples were labeled using the same standardized protocols.…”
Section: Methodsmentioning
confidence: 99%
“…This enzyme has recently been reestablished as a potential treatment to counteract RT-qPCR inhibition in the analysis of miRNA in plasma. 15,22 To develop more general standards and optimize incubation conditions for RNA isolated from urine, heparinase I was added in different concentrations during cDNA synthesis. The effect of heparinase I treatment was assessed using the PCR results from spiked-in miRNA Cel-miR-39 and the endogenous miRNAs miR-30e and miR-92a.…”
Section: Heparin Is a Potent Inhibitor Of Rt-qpcr Analysis In Urinarymentioning
confidence: 99%
“…For example, Izraeli et al, 24 reported that 1-3 units of heparinase I for 2 hours at 25°C yielded successful PCR amplification, but no optimization of the procedure is described. More recently, Plieskatt et al 9 , described a protocol to RT-PCR amplify microRNAs isolated from heparinized blood samples using 6U of heparinase I during 1-2 h, either as a pre-treatment at 25°C or during the RT reaction at 37°C without testing whether the variables of time, temperature, or enzyme type could be optimized. An interesting alternative procedure to remove heparin from RNA preps is described by Ding et al 25 , who observed that an ultracentrifugation step prior to RNA extraction improved PCR-based amplification of viral nucleic acids from plasma.…”
Section: Discussionmentioning
confidence: 99%
“…9 However the authors did not optimize variables such as time, temperature, or performance of different types of Bacteroides heparinase. We have developed a low-cost colorimetric assay to monitor heparin removal and to determine optimal enzymatic or adsorption-dependent effective reduction of heparin levels below assay interference levels, for the processing of human blood fractions in assays affected by the presence of this anticoagulant.…”
Section: Among Othersmentioning
confidence: 99%